Reaction of Hydrogen and Oxygen on h-BN - Späth, Florian; Steinhauer, Johann; Düll, Fabian; Bauer, Udo; Bachmann, Philipp; Steinrück, Hans-Peter; Papp, Christian (Journal of Physical Chemistry C, 2020)
We report the reversible functionalization of hexagonal boron nitride (h-BN) on Ni(111) with a molecular oxygen species and atomic hydrogen, as studied by high-resolution X-ray photoelectron spectroscopy, ultraviolet photoelectron spectroscopy, and near-edge X-ray absorption fine structure. As a first step, we prepare oxygen-functionalized h-BN by exposure to a supersonic beam of molecular oxygen. Subsequent exposure to atomic hydrogen leads to complete removal of the oxygen species and the formation of hydrogen-functionalized h-BN. In turn, this hydrogen-functionalized h-BN can be reconverted to oxygen-functionalized h-BN by exposure to the supersonic oxygen beam. This reaction occurs at a lower rate as the initial functionalization of pristine h-BN with oxygen. We further demonstrate that the core levels and valence bands of h-BN can be shifted at will between the boundaries obtained for the purely oxygen- and hydrogen-functionalized h-BN layers.
CRIS-Team WoS Importer:2020-09-18